Strategic reclamation policy of post-mining area based in the enviroment in North Kolaka district. Issue 1 (October 2020) - Hartono, Budi; Imran, A M; Rijal Idrus, M
Abstract: This paper aims to investigate the absence of reclamation activities and its objectives regarding the appropriate policies of friendly environmental post-mining area that happened in mining companies, North Kolaka District. The Stakeholder analysis applies Analytical Hierarchy Process (AHP) method along with Expert Choice software, version 11, to obtain the weight of pairwise comparison matrix. Based on the elements of structural hierarchy, the results of weighting and priorities can be constructed to get the strategic policy of mine secondary reclamation. The determined priority values for each element are obtained from the calculation of responses given by stakeholders who are considered to have a stake in the management, so that the level of contribution can be distinguished. The strategic reclamation of secondary nickel mines has obtained a sustainable and friendly environmental management policy whereas the reclamation area strategy includes economic benefits for the local people. As for the natural resources toward non-renewable mining, the ecological condition happens to be the initial concern of stakeholders.